Sclerodermiform basal cell carcinomas vs. other histotypes: analysis of specific demographic, clinical and dermatoscopic features. (5th June 2020) - Conforti, C.; Pizzichetta, M.A.; Vichi, S.; Toffolutti, F.; Serraino, D.; Di Meo, N.; Giuffrida, R.; Deinlein, T.; Giacomel, J.; Rosendahl, C.; Gourhant, J.Y.; Zalaudek, I.
Abstract: Background: Among the various types of basal cell carcinoma, the sclerodermiform variant has a high risk of recurrence and local invasiveness. A systematic description of the dermatoscopic features associated with specific body localization is lacking. Objectives: To describe the clinical and dermoscopic features of sclerodermiform basal cell carcinoma (BCC) according to localization in the body confronting with superficial and nodular types. Methods: Clinical and dermoscopic images of sclerodermiform, nodular and superficial BCCs were retrospectively evaluated to study the location in the various body districts, maximum diameter, clinical appearance of the lesion, features of edges and presence or absence of specific dermatoscopic criteria of BCCs. Results: We examined 291 histopathologically proven BCCs showing that in nodular BCCs, classical arborizing vessels were more frequently found in the body macro‐area (trunk and limbs; n = 46, 97.9%) than in the head/neck area ( n = 43, 82.7%); within sclerodermiform BCCs, short arborizing vessels were found more frequently in the head/neck district ( n = 35, 49.3%) than in the body ( n = 6, 23.1%; P ‐value 0.02); within nodular BCCs, multiple blue‐grey dots and globules were more frequently found on the trunk ( n = 23, 48.9%) than in the head/neck district ( n = 12, 23.1%; P ‐value 0.01). In sclerodermiform BCCs, ulceration was found more frequently in the head/neck district ( n = 38, 53.5%) than in the body ( n = 4, 15.4%; P ‐value > 0.01), and in superficial BCCs, ulceration was found more frequently in the head/neck district ( n = 5, 38.5%) than in the body ( n = 8, 9.8%; P ‐value 0.02). Conclusion: Our study shows that superficial BCC are found frequently in the head/neck district dermoscopically characterized by ulceration and arborizing vessels; nodular BCCs are more frequently found in the body than in the head/neck district, and the dermoscopic pattern is characterized by the combination of three features: (i) classical arborizing vessels, (ii) multiple blue‐grey dots and (iii) globules. Instead, sclerodermiform BCC is preferentially located in areas at high–moderate risk of recurrence; if pink‐white areas and/or fine arborizing vessels are seen, clinicians should consider this diagnosis. Furthermore, location‐specific dermatoscopic criteria have been described.